SPECIFIC LANGUAGE TYPES OF RELIGIOUS STYLE - Adina Elena Coclici (Telescu) (Studii si Cercetari Filologice: Seria Limbi Straine Aplicate, 2011)
The purpose of this article is to investigate the specific languages of religious style, including the common and the newer ones. The religious style is the first special manifestation of the Romanian literary language; and the beginning of the written Romanian language is directly associated with the writing of religious texts. Being ignored for a long time, in the last decades, the religious style assumed new forms generated by the practices of religious rites, which are sometimes very diversified. The article describes the main language types, and we mention the following: the biblical language, the liturgical language, religious oratorical, religious tehnical, religious dramatical, theological or the ecclesiastic magazine language. The biblical language predominates in Romanian culture through its primary and most conservative version, the biblical text, as opposed to the theological language, which underwent modification during the modernization of the Romanian literary language. The religious oratorical language of the sermons distinguish itself being more mobile, using frequently means that are characteristic to the fictional style languages. The language of the theological magazines derives from the theological language and it points only to the theological version of religious style and not the style on the whole. Therefore, the language of the contemporary ecclesiastical texts carries forward our old literary language that was used in the first decades of the 19th century. The ecclesiastical literature had a major role in the development of the Romanian literary language, a role that was emphasized in number of studies. The multitude of language types of religious style proves that this stylistic version has been existing since back in the old Romanian language period.